(untitled) (Research, Society and Development, 2020)
This study aims to determine the potential of three organic compounds in the preparation of substrates for the production of BRS Kurumi elephant seedlings from minitoletes. The residues utilized in the compostings were: sugarcane bagasse and straw, sawdust, bovine manure, acacia bark, aviary bedding and tung cake. For the formulation of the substrates we added different proportions of rice husk ash and carbonized rice hull to the compounds, resulting in 12 substrates. A commercial substrate was used as control. The compounds were classified based on nutrient quantities, pH, electrical conductivity and pathogens. The agronomic efficiency tests of the substrates were conducted in a Embrapa Clima Temperado greenhouse, lasting 50 days. The agronomic variables evaluated were budding percentage, number of leaves, root collar diameter, shoot height, dry mass of the shoot and root, shoot and root dry mass ratio and stability of the clod. The results show that two organic compounds are proper for use in agriculture in accordance with the maximum limits of pathogens established by legislation. The substrates based on organic compounds produced equal or superior results to the commercial substrate, with the 100% organic compound 2 substrate and the 75% organic compound 2 + 12,5% rice husk ash + 12,5% carbonized rice hull substrate showing the most potential for the production of seedlings of the studied species.